Bioinspired l‑Proline Oligomers for the Cryopreservation of Oocytes via Controlling Ice Growth - Qin, Qingyuan; Zhao, Lishan; Liu, Zhang; Liu, Tao; Qu, Jiangxue; Zhang, Xiaowei; Li, Rong; Yan, Liying; Yan, Jie; Jin, Shenglin; Wang, Jianjun; Qiao, Jie (ACS applied materials & interfaces, 2020)
Various types of cells are routinely cryopreserved in modern regenerative and cell-based medicines. For instance, the oocyte is one of the most demanding cells to be cryopreserved in genetic engineering and human-assisted reproductive technology (ART). However, the usage of cryopreserved oocytes in ART clinics is still limited mainly because of the unstable survival rate. This is due to the fact that oocytes are more prone to be damaged by ice crystals in comparison to other cells, as oocytes are larger in size and surface area. Meanwhile, oocytes contain more water, and thus, ice crystals are easier to form inside the cells. Currently, to avoid injury by the formed ice crystals, cryopreservation (CP) of oocytes has to use large amounts of small molecules as cryoprotectants such as dimethyl sulfoxide (DMSO) and ethylene glycol (EG), which can permeate into the cell and prevent ice formation inside. However, these molecules are chemically and epigenetically toxic to cells. Therefore, great efforts have been focused on reducing the amount of DMSO and EG used for oocyte CP. In nature, the antifreeze (glyco)proteins (AFGPs) locate extracellularly with the ability to protect living organisms from freezing damage via controlling ice growth. Inspired by this, biocompatible and nontoxic L-proline oligomers (L-Pro n ), which have the same polyproline II helix structure as that of AFGPs, are first employed for the CP of oocytes. The experimental results reveal that L-Pro8 has a profound activity in inhibiting ice growth as that of AFGP8. Also, by the addition of 50 mM L-Pro8, the amount of DMSO and EG can be greatly reduced by ca. 1.8 M for oocyte CP; moreover, the survival rate of the cryopreserved oocytes is increased up to 99.11%, and the coefficient of variance of the survival rate is decreased from 7.47 to 2.15%. These results mean that almost all oocytes can survive after CP with our method; importantly, the mitochondrial function as a critical criterion for the quality of the frozen–thawed oocytes is also improved. It is proposed that with the addition of L-Pro8, the extracellular ice growth is slowed down, which prevents the direct injuries of cells by large ice crystals and the accompanying osmotic pressure increase. As such, this work is not only significant for meeting the ever-increasing demand by the ART clinics but also gives guidance for designing materials in controlling ice growth during CP of other cells and tissues.